Organocatalysts for the Synthesis of Poly(ethylene terephthalate‐co‐isosorbide terephthalate): A Combined Experimental and DFT Study. Issue 9 (25th June 2019) - Stanley, Nicholas; Chenal, Thomas; Jacquel, Nicolas; Saint‐Loup, René; Prates Ramalho, Joao Paulo; Zinck, Philippe
Abstract: Organocatalysts are assessed for the insertion of isosorbide, a rigid, biobased diol monomer, into poly(ethylene terephthalate). A sulfonic acid (p‐toluenesulfonic acid—APTS), an amidine base (1, 8‐diazabicyclo [5.4.0] undec‐7‐ene—DBU) and a guanidine base (1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene—TBD) successfully catalyze the polymerization. The reaction mechanisms are studied by density functional theory. A bifunctional activation is observed in the presence of the sulfonic acid, the carbonyl moiety being activated via the acidic proton of APTS and the alcohol via the basic oxygen. Regarding DBU, a mechanism based on a basic activation of the alcohol rather than a nucleophilic attack of the catalyst is evidenced. The difference observed between TBD and DBU is attributed to a better H‐bonding ability of the former versus the latter. Abstract : Organocatalysts are successfully assessed for the insertion of isosorbide into polyethylene terephthalate. The reaction mechanisms are studied by density functional theory.